Tratamento enzimático com laccase associada a catecóis na molhabilidade, adesão de células e atividade antimicrobiana em substratos de poli(éter-éter-cetona) - Nascimento, Matheus Vieira (2021)
Previous studies suggest poly(ether-ether-ketone) (PEEK) as a potential alternative to titanium implants because of its satisfactory aesthetic and mechanical characteristics. However, its polymeric nature hinders osseointegration, which could be overcome with enzymatic treatment combining laccase and catechols. This study aimed to evaluate the effects of treatment with laccase associated with catechols on wettability, cell adhesion, and antimicrobial activity of PEEK substrates. PEEK discs (15 x 2 mm) were cut and randomly distributed in treatment groups (n = 3): controls - acetate solution (Ac), laccase enzyme (Lc) and catechols (dopa, DOc dopamine DMc; and caffeic acid ACc); experimental - laccase + dopa (LDO), laccase + dopamine (LDM) and laccase + caffeic acid (AC). All substances were individually diluted in acetate solution pH 4.75 at 0.5 mg/mL at room temperature and kept in contact with PEEK substrates for 18 hours. Changes in wettability were measured by water contact angle (WCA) 0, 10, 30 minutes, 1, 2, 4 hours 1, 2, 5, 7, 14, 21, and 30 days after treatments. The cell density (cells / mm²) of osteoblast-like cells (MG-63) was measured after 24 hours of contact, with eosin-hematoxylin staining under optical microscopy. Antimicrobial activity against S. aureus (ATCC 25923) and E. coli (ATCC 11205) was performed by counting the colony-forming units (CFU/mL) after 24 hours of contact. The data were analyzed with one-way ANOVA and ANOVA of repeated measures submitted to the post-tests of Dunnet, Sidak, and Tukey, and linear trend analysis was also performed (α = 0.05). All treatments significantly decreased the WCA of the samples compared to the acetate control (Ac - 85.6º ± 0.6; p <0.0001) at all times evaluated. The groups treated with laccase+catechols had the lowest WCA, with an emphasis on LDM at T = 0min (18.5º ± 2.3). The groups treated with laccase + catechol exhibited higher cell density of MG 63 than the group treated with Lc (p <0.05), as well as with the control group Ac acetate (p <0.05). There was no statistical difference between the control and treated groups in the reduction of CFU for both S. aureus and E. coli (p> 0.05). The surface treatment with laccase associated with catechols significantly decreased the contact angle of the PEEK substrates and improved the adhesion of MG-63, although it did not show antimicrobial activity against S. aureus and E. coli.